Reducing inter-unit pollutant transfer through multifamily unit compartmentalization - Scott W. Adler; Deborah H. Bennett; Mark P. Modera (Elsevier, 2024)
Compartmentalization, which refers to air sealing each unit within a building from the exterior and other interior spaces, has been proposed as a strategy to improve indoor air quality and energy efficiency in multifamily buildings. This study collected field data on air tightness and pollutant transfer in three new-construction multifamily buildings in California, which was used to develop a model in CONTAM that simulated the impact of leakage levels, ventilation strategies, and climate zones on inter-unit pollutant transfer in multifamily buildings. Air leakage testing found an average total unit leakage of 0.8 L/s50/m2, almost twice as tight as California's current compartmentalization requirement (1.5 L/s50/m2). Two buildings designed with balanced ventilation systems were measured to have imbalanced continuous unit ventilation flows, which were further imbalanced by intermittent exhaust fan operation. Tracer gas testing in two buildings indicated that only about 1-3% of the total air entering a unit came from each neighbouring unit. Furthermore, all particles were apparently removed along the way, as there was no observable particle matter transfer at the tested air tightness levels (0.6-0.9 L/s50/m2). Modelling results indicated that leakier units led to greater dilution of pollutants generated within the unit but increased gaseous pollutant transfer from neighbouring units. The average concentration of benzene, a proxy gas for cigarette smoke, transferred into non-smoking units from neighbours who did smoke almost doubled, surpassing acceptable exposure levels, in the leaky simulation (2.3 L/s50/m2) compared to the tight simulation (0.8 L/s50/m2). Overall, this study suggests that stricter compartmentalization requirements should be adopted in multifamily building code updates, as tighter requirements appear to be manageable for builders and beneficial for indoor air quality when combined with mechanical ventilation.